CHINA'S SOCIAL AND ECONOMIC TRANSFORMATION AND ECONOMIC INEQUALITY IN THE ERA OF MODERN TECHNOLOGIES (INNOVATIVE ECONOMY, 2025)
Wu Qi.  CHINA'S SOCIAL AND ECONOMIC TRANSFORMATION AND ECONOMIC INEQUALITY IN THE ERA OF MODERN TECHNOLOGIESPurpose. The aim of this article is to analyse of the social and economic transformation of the People's Republic of China from a long-term historical perspective, assess the current state of the Chinese economy, and identify the key factors and challenges influencing the implementation of its strategic directions of development in conditions of global instability.Methodology of research. The research employed general scientific and specialized methods, including induction and deduction – at the stage of collecting, systematizing, and processing the necessary information; elements of correlation and regression analysis and visualization of the dynamics of key indicators.Findings. It was established that the social and economic transformation of China was accompanied by significant changes in the structure of GDP, employment, the educational level of the population, urbanization, and foreign trade, which had a direct impact on the level of social inequality. In particular, a positive dynamic was observed in the growth of the proportion of the population with higher education, which contributed to the formation of a new middle class and the enhancement of labour competitiveness. At the same time, the growth of regional disparities and uneven access to quality education and social services became a source of deepening social and economic differentiation. The conducted correlation and regression analysis confirmed the close relationship between the level of education, urbanization, and income levels, and demonstrated that regions with higher levels of education and innovation activity have lower levels of social inequality. The comparative analysis allowed for outlining the key stages of the evolution of China’s economic model: from a centralized planned economy to a hybrid model with market mechanisms, which includes elements of social protection. This, in turn, enabled the country to achieve high rates of economic growth while maintaining social stability.Originality. The article proposes a new analytical model that enables the tracing of the relationship between structural shifts in the economy and the increase (or decrease) in social inequality across specific regions of China. For the first time, data from 2022–2023 on changes in the demographic and educational structure of the population are also integrated into the analysis of the factors shaping the current profile of the country's human capital.Practical value. The results of the study have significant practical implications for the development of effective social and economic policies in countries undergoing deep transformation. The proposed analytical model can be used as a tool to assess the impact of structural changes in the economy on the level of social inequality, particularly in the process of planning regional development, reforming the education and employment systems. The conclusions drawn can serve as a basis for adapting China's experience to the conditions of other countries aiming to combine economic growth with the enhancement of social justice. Furthermore, the results can be applied in scientific research, education, and analytical activities for further exploration of issues related to inequality and human development.Key words: social inequality, economic inequality, transformation, China, GDP structure, employment, urbanization, education, economic growth.
Keywords: social inequality; economic inequality; transformation; China; GDP structure; employment; urbanization; education; economic growth